AN UPDATE ON BIO-POTENTIATION OF DRUGS USING NATURAL OPTIONS - SAXENA, VASUNDHARA; SINGH, AYUSHI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
The objective of this review is to put a light on the benefits of bio-enhancers and their role in developing a proper drug delivery system having improved therapeutic action and least drawbacks. As medical science is developing fast and there is a considerable increase in the development of new drugs with many therapeutic activities, but having lots of side effects, less in vivo action, or are very costly. These drawbacks create an enormous demand for use of bio-enhancers to reduce the dose required of the active ingredients and provide a suitable condition for their actions. There are vast nature-derived bio-enhancers originated from plants or other natural sources, used to a great extent as they show high activity and have very little or no adverse effects. Bio-enhancers increase bioavailability in various ways such as by increasing drug absorption, decreasing drug metabolism, and by other methods, which helps the drug having low bioavailability but the good therapeutic potential to show its effect fast. The concept of bio-enhancers developing increasingly in modern medicine but in reality, was there and well explained in Ayurveda texts with various herbal drugs such as piperine, quercetin, genistein, naringin and some non-herbal compounds such as cow urine distillate, and Capmul. Along with these nature-derived bio-enhancers and the new techniques such as liposomes, nanoparticles, transferosomes, and ethosomes resulted in the successful modification of suitable dosage forms. The concept of bioenhancers and their application is a great tool which can lead to a excellent development of medical science.